Daylighting the New York Times Headquarters Building: Final Report - Eleanor S. Lee; Stephen E. Selkowitz; Glenn D. Hughes; Robert D. Clear; Gregory J. Ward; John Mardaljevic; Judy Lai; Mehlika Inanici; Vorapat Inkarojrit (2005)
The technical energy-savings potential for smart integrated window-daylighting systems is excellent and can yield significant reductions in US commercial building energy use if adopted by a significant percentage of the market. However, conventional automated shades and daylighting controls have been commercially available for over two decades with less than 1-2% market penetration in the US. As with all innovations, the problem with accelerating market adoption is one of decreasing risk. As the building owner researches technology options, the usual questions surface that concern the purchase of any new product: how will it work for my application, are the vendor claims valid, what risks are incurred, and will the performance benefits be sustained over the life of the installation? In their effort to create an environment that "enhances the way we work" in their new 139 km2 (1.5 Mft2) headquarters building in downtown Manhattan, The New York Times employed a unique approach to create a competitive marketplace for daylighting systems. A monitored field test formed the strategic cornerstone for accelerating an industry response to the building owners' challenge to a sleepy market (i.e., US automated shading and daylighting control products have had few major technical advances over the past 10 years). Energy, control system, and environmental quality performance of commercially-available automated roller shade and daylighting control systems were evaluated. Procurement specifications were produced. Bids were received that met The Times cost-effective criteria. The Times will proceed with the use of these systems in their final building. Competitively-priced new products have been developed as a result of this research and are now available on the market.
Keywords: automated daylighting controls; automated window shades; daylighting; energy-efficiency; visual comfort

A Method for Simulating the Performance of Photosensor-Based Lighting Controls - Charles K. Ehrlich; Konstantinos M. Papamichael; Judy Lai; Kenneth L. Revzan (Energy and Buildings, 2001)
The unreliability of photosensor-based lighting controls continues to be a significant market barrier that prevents widespread acceptance of daylight dimming controls in commercial buildings. Energy savings from the use of daylighting in commercial buildings is best realized through the installation of reliable photoelectric lighting controls that dim electric lights when sufficient daylight is available to provide adequate background and/or task illumination. In prior work, the authors discussed the limitations of current simulation approaches and presented a robust method to simulate the performance of photosensor-based controls using an enhanced version of the radiance lighting simulation package. The method is based on the concept of multiplying two fisheye images: one generated from the angular sensitivity of the photosensor and the other from a 180 or 360 deg. fisheye image of the space as seen by the photosensor. This paper includes a description of the method, its validation and possible applications for designing, placing, calibrating and commissioning photosensor-based lighting controls.

Simulating the Operation of Photosensor-Based Lighting Controls - Charles K. Ehrlich; Konstantinos M. Papamichael; Judy Lai; Kenneth L. Revzan (2001 Building Simulation 7th International Building Performance Simulation Association Conference, 2001)
Energy savings from the use of daylighting in commercial buildings are realized through implementation of photoelectric lighting controls that dim electric lights when sufficient daylight is available to provide adequate workplane illumination. The dimming level of electric lighting is based on the signal of a photosensor. Current simulation approaches for such systems are based on the questionable assumption that the signal of the photosensor is proportional to the task illuminance. This paper presents a method that simulates the performance of photosensor controls considering the acceptance angle, angular sensitivity, placement of the photosensor within a space, and color correction filter. The method is based on the multiplication of two fisheye images: one generated from the angular sensitivity of the photosensor and the other from a 180- or 360-degree fisheye image of the space as seen by the photosensor. The paper includes a detailed description of the method and its implementation, example applications, and validation results based on comparison with measurements in an actual office space.